Multiple oral Candida infections in patients with Sjogren's syndrome -- prevalence and clinical and drug susceptibility profiles - Yan, Zhimin; Young, Andrew L; Hua, Hong; Xu, Yanying (Journal of rheumatology, 2011)
To determine the prevalence of oral candidiasis and multiple oral Candida infections in patients with primary Sjögren's syndrome (SS), and the clinical and drug susceptibility profile. Thirty patients with primary SS were enrolled in our study. The diagnosis of oral candidiasis was based on the clinical manifestation, and confirmed by a concentrated rinse culture. Candida spp. assessment was accomplished using standard methods: Sabouraud dextrose agar with 50 mg/l chloramphenicol and CHROMagar were used for the rapid screening of clinical species, followed by the API 20C system for further species identification. In vitro antifungal drug susceptibility of Candida isolates was determined by the minimal inhibitory concentrations. In our study, 87% (26/30) of subjects had oral candidiasis, in which 42% (11/26) had multiple Candida spp. infection. Although C. albicans remains the predominant isolate, other rare species such as C. tropicalis, C. glabrata, C. parapsilosis, and C. krusei were present, alone or in combination. Chronic atrophic candidiasis is the most common clinical type of oral candidiasis in patients with SS. The susceptibilities of the 44 Candida isolates to 7 antifungal agents varied dramatically. The resistance to azoles was remarkable, and the phenomenon of cross-resistance between itraconazole and fluconazole was observed. Patients with primary SS carry a high risk of oral candidiasis and a high frequency of multiple Candida infections. The azole resistance patterns of Candida spp. support the necessity for drug susceptibility testing as a routine procedure for patients with oral Candida infections.